2007
DOI: 10.1002/hep.21533
|View full text |Cite
|
Sign up to set email alerts
|

Lactulose improves cognitive functions and health-related quality of life in patients with cirrhosis who have minimal hepatic encephalopathy

Abstract: Minimal hepatic encephalopathy (MHE) has a negative effect on patients' daily functioning. Thus far, no study has investigated the effect of treatment-related improvement in cognitive functions on health-related quality of life (HRQOL). We measured psychometric performance by number and figure connection tests parts A and B, picture completion, and block design tests and HRQOL by the Sickness Impact Profile (SIP) of 90 patients with cirrhosis on inclusion into the study and 3 months later. A Z score less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
466
2
6

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 525 publications
(493 citation statements)
references
References 46 publications
(77 reference statements)
11
466
2
6
Order By: Relevance
“…Prevalence of MHE in our population varies between 48% and 67.7% as shown by our previous studies using psychometric tests. 2,10,11 Patients who develop MHE are …”
mentioning
confidence: 99%
“…Prevalence of MHE in our population varies between 48% and 67.7% as shown by our previous studies using psychometric tests. 2,10,11 Patients who develop MHE are …”
mentioning
confidence: 99%
“…The results of this study indicate that future trials with targeted prebiotics and probiotics should aim at enhancing cognition through modulation of these microbiome components. 3,11 There were no significant differences in the fecal microbiome families between the HE and no HE groups except a significantly higher abundance of Veillonellaceae in the HE group. Also, lactulose withdrawal did not change the microbiome significantly except for reduction in Faecalibacterium sp.…”
Section: Microbial Analysis Between Controls and Patients With Cirrhosismentioning
confidence: 88%
“…9,10 Current treatments for HE, such as lactulose, antiobiotics and others also rely on manipulation of the gut flora. 11,12 Culture-based techniques were used for the characterization of gut flora in prior HE studies. 9,13 Recently, Bajaj and co-workers have published 3 studies related to gut microbiota, inflammation and cognition in hepatic encephalopathy.…”
Section: Gut Flora Systemic Inflammation and Hepatic Encephalopathymentioning
confidence: 99%
“…23 In a randomized open label trial, lactulose therapy 30-60 mL/day was compared to no treatment in patients with cirrhosis and MHE. 24 Compared to the untreated group, there was a significant decrease in the number of abnormal psychometric tests in the group treated with lactulose (P < 0.0001). Treatment also demonstrated a significant improvement in the health-related quality of life (HRQoL) vs. those who did not receive lactulose [6.81 vs 0.17 (95% CI, 5.24-8.37) and (95% CI, À0.29 to 0.63), respectively; P < 0.001].…”
mentioning
confidence: 84%
“…Treatment also demonstrated a significant improvement in the health-related quality of life (HRQoL) vs. those who did not receive lactulose [6.81 vs 0.17 (95% CI, 5.24-8.37) and (95% CI, À0.29 to 0.63), respectively; P < 0.001]. 24 Sharma et al further reported the benefit of lactulose therapy for the primary prevention of OHE in patients with cirrhosis. A total of 120 cirrhotic patients with no prior episode of OHE were randomized to receive lactulose (55 patients, 32/55 with MHE) or no treatment (50 patients, 36/50 with MHE), with progression to OHE assessed over 12 months.…”
mentioning
confidence: 99%